Population vital rates of resident and translocated female greater sage‐grouse. Issue 4 (28th March 2016) - Gruber‐Hadden, Natasha W.; Messmer, Terry A.; Maxfield, Brian D.; Koons, David N.; Guttery, Michael R.
ABSTRACT: Translocations have been recommended to reestablish, augment, and sustain genetic diversity in declining wildlife populations, including greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse). Characteristics of successful sage‐grouse translocations include suitable contiguous sagebrush ( Artemisia spp.), seasonal habitats surrounded by geomorphic barriers, a residual resident population, and pre‐nesting releases. From 2009 to 2010, we studied vital rates of 60 translocated and 15 resident radio‐marked female sage‐grouse and their broods on Anthro Mountain, in the Ashley National Forest, northeastern Utah, USA to determine whether translocations could augment a declining meta‐population that inhabited suitable breeding habitats in a small spatially isolated landscape. Survival rates, and nest and brood success estimates for the resident and translocated sage‐grouse we studied were lower than reported range‐wide averages. Nest success was similar for resident and translocated birds (survival estimate: 0.468, 95% CI = 0.288–0.648) and we calculated weak, yet positive relationships to grass height and grass cover. Daily survival rates for chicks 0–19 days of age for resident females in 2009 (0.904, CI = 0.875–0.940) and in 2010 (0.910, CI = 0.888–0.945) were higher than for chicks raised by translocated females (0.883, CI = 0.850–0.915; 0.892, CI = 0.856–0.936, respectively), although differences were small and all 95% confidence intervals had substantial overlap. In 2009 and 2010, daily survival rates for chick 20–50 days of age were slightly higher for chicks reared by resident females (0.980, CI = 0.963–0.994; 0.998, CI = 0.978–1.000, respectively) than chicks reared by translocated females (0.877, CI = 0.623–0.959; 0.988, CI = 0.945–0.993, respectively). Chick survival for both groups was weakly correlated with grass cover. Although most translocated birds remained on the study area (82%), the low overall survival rates we report indicate that managers need to consider factors affecting survival of adult females, nests, and chicks when planning future translocations to augment sage‐grouse meta‐populations that occupy spatially isolated and space‐limited habitats. © 2016 The Wildlife Society.